Konsistensi Konsep Keselamatan adalah Anugerah dalam Masa Intertestamental - Putri, Agustin Soewitomo (MAGNUM OPUS: Jurnal Teologi dan Kepemimpinan Kristen, 2020)
The period between the Old Testament and the New Testament is often referred to as the intertestamental period which is approximately 400 years apart, during which time no prophet appears to be the successor of God's voice. Ended by the prophet Malachi and the book of Chronicles the Bible does not give any record. This certainly raises so many questions as to what happened in that dark age, whether God really did not do anything among God's people, especially the Israelites, while at that time the Israelites had repeatedly experienced good colonization from Persian, Greek or Roman. By using descriptive methods and historical analysis, this discussion will provide an insight into God's faithfulness to His covenant to the people, and how the concept of salvation has not changed even though in the 400 years that God did not speak to His people. Understanding the consistency of the concept of salvation is a gift in intertestamental times will open a new understanding of the power of God in keeping the covenants and His Word.AbstractMasa antara Perjanjian Lama dengan Perjanjian Baru seringkali disebut dengan masa intertesta-men yang berjarak lebih kurang 400 tahun, di mana sepanjang masa tersebut tidak ada nabi yang muncul menjadi penerus suara dari Tuhan. Diakhiri oleh Nabi Maleakhi dan kitab Tawarikh maka Alkitab tidak memberikan catatan apa pun. Hal tersebut tentu memunculkan begitu banyak pertanyaan dengan apa yang terjadi dalam masa kegelapan tersebut, apakah memang Allah betul-betul tidak berbuat sesuatu apapun di tengah-tengah umat Tuhan, khususnya bangsa Israel, sementara pada masa tersebut bangsa Israel berkali-kali mengalami penjajahan baik dari Persia, Yunani ataupun Romawi. Dengan menggunakan metode deskriptif dan analisis historis, pemba-hasan ini akan memberikan pandangan tentang kesetiaan Allah dengan perjanjianNya kepada umat, serta bagaimana konsep keselamatan itu tidak mengalami pergeseran sekalipun dalam keadaan 400 tahun Tuhan tidak berbicara kepada umatNya. Memahami konsistensi konsep keselamatan adalah anugerah dalam masa intertestamental akan membukakan pemahaman baru tentang kekuatan Allah dalam memelihara perjanjian dan FirmanNya.